Inequality, Control Rights, and Rent Seeking: Sugar Cooperatives in Maharashtra - Banerjee, Abhijit; Mookherjee, Dilip; Munshi, Kaivan; Ray, Debraj (Journal of Political Economy, 2001)
This paper presents a theory of rent seeking within farmer cooperatives in which inequality of asset ownership affects relative control rights of different groups of members. The two key assumptions are constraints on lump‐sum transfers from poorer members and disproportionate control rights wielded by wealthier members. Transfers of rents to the latter are achieved by depressing prices paid for inputs supplied by members and diverting resulting retained earnings. The theory predicts that increased heterogeneity of landholdings in the local area causes increased inefficiency by inducing a lower input price and a lower level of installed crushing capacity. Predictions concerning the effect of the distribution of local landownership on sugarcane price, capacity levels, and participation rates of different classes of farmers are confirmed by data from nearly 100 sugar cooperatives in the Indian state of Maharashtra over the period 1971–93.